Un uso sostenibile delle risorse idriche con dati telerilevati e software Open Source (GEOmedia, 2009)
Sustainable agricultural water use by means of open source decision support systems and Earth Observation data.The PLEIADeS project (funded by European VI Framework Program) addresses the improvement of water use and management in agriculture through innovative Information Technologies and the most recent Earth Observation (EO) methodologies. Within this framework a tool, based on Open Source software, which aims at helping water managers to optimize the water consumption, has been realized. One of the key features of the system is the delivering of a near real-time irrigation schedule to farmers produced through the integration of EO-derived product and fi eld data inside a GIS environment that provides a reliable crop requirement estimation at farm level.